Hubungan Efikasi Diri dan Dukungan Sosial Dengan Tingkat Stres Mahasiswa Akhir - Viki Anggraini; Dewi Lutfianawati; Supriyati Supriyati (Program Studi Psikologi Islam, 2026)
Abstract Final-year students are vulnerable to academic stress due to the demands of completing a final project, time pressure, and academic and social expectations. Academic stress that is not properly managed can negatively affect students’ psychological well-being and academic performance. This study aims to examine the relationship between self-efficacy and social support and the stress levels of final-year students. This study employed a quantitative method with 184 final-year students as participants, selected using a convenience sampling technique. Data were analyzed using multiple regression analysis with the assistance of IBM SPSS Statistics version 27. The results indicate that self-efficacy and social support significantly contribute to the stress levels of final-year students, with a contribution value of 22,23%. This study emphasizes that enhancing self-efficacy and providing adequate social support play an important role in helping reduce stress levels among final-year students. Keywords: self-efficacy, social support, stress levels of final-year students.